The reliability and validity of protocols for the assessment of endurance sports performance: An updated review - Stevens, C. J.; Dascombe, B. J. (Measurement in Physical Education and Exercise Science, 2015)
Sports performance testing is one of the most common and important measures used in sport science. Performance testing protocols must have high reliability to ensure any changes are not due to measurement error or inter-individual differences. High validity is also important to ensure test performance reflects true performance. Time-trial protocols commonly have a coefficient of variation (CV) of <5%, however, familiarization, well-trained subjects and/or conducting the trial outdoors in the athlete`s most familiar environment can lead to CVs of < 1%. Long duration time-trials or the inclusion of sprints within a time-trial appears to not negatively influence reliability. Few studies have assessed the validity of endurance performance tests, and as such more research should evaluate different ways of simulating outdoor performances in the laboratory. The use of warm-up, simulation of convection load, and implementation of race specific hydration practices are important considerations for researchers regarding test validity. ABSTRACT FROM AUTHOR